2020
DOI: 10.1136/bmjdrc-2019-000879
|View full text |Cite
|
Sign up to set email alerts
|

Long-term BMI change trajectories in Chinese adults and its association with the hazard of type 2 diabetes: evidence from a 20-year China Health and Nutrition Survey

Abstract: IntroductionTo investigate the relationship between long-term change trajectory in body mass index (BMI) and the hazard of type 2 diabetes among Chinese adults.Research design and methodsData were obtained from the China Health and Nutrition Survey (CHNS). Type 2 diabetes was reported by participants themselves in each survey wave. The duration of follow-up was defined as the period from the first visit to the first time self-reported type 2 diabetes, death, or other loss to follow-up from CHNS. The patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Many studies have shown that obesity or overweight in childhood is likely to persist into adulthood [3][4][5][6][7]. Childhood obesity can lead to various health problems, even premature death [8][9][10]. Obesity and overweight have imposed a heavy economic burden on China and induces considerable medical expenditures each year [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that obesity or overweight in childhood is likely to persist into adulthood [3][4][5][6][7]. Childhood obesity can lead to various health problems, even premature death [8][9][10]. Obesity and overweight have imposed a heavy economic burden on China and induces considerable medical expenditures each year [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from large-scale prospective studies suggested that population with stable weight tended to have higher socioeconomic position, healthier lifestyle factors and consumed a healthier diet than those in weight change groups 26 , 30 . According to these studies and a priori knowledge about our data (results from the association between weight change pattern and risk of type 2 diabetes) 36 , a set of covariates were considered as potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to report their current status of smoking in each wave, and were assigned to never or current smoker according to their answer to the question “Have you ever smoked cigarettes (including hand-rolled or device-rolled)” 36 , 37 . Alcohol consumption was classified into never or current, similar to smoking.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations